A virtual ‘experiential expert’ communities of practice in sharing evidence based prevention of novel psychoactive substance (NPS) use: the portuguese experience - Henriques, Susana (2020)
We present findings from a unique virtual community of practice piloted to support a programme of prevention evidence and knowledge sharing among professional prevention practitioners as ‘experiential experts’ around tackling novel psychoactive substances (NPS) use in Portugal. A mixed-methods approach that combined quantitative analysis of interactions and qualitative content analysis of debates about NPS, NPS users, patterns of use and best practices in prevention of this type of drug use was conducted. Results show low and irregular interactions between members of this virtual community, but very rich discussions around sharing of experiences and problematizing practices. We discuss the layers of interaction between members, and the shared learning around policy and practice implications. Such virtual and collaborative work practices are not yet integrated within the drug prevention field where instead individualistic approaches tend to prevail and preclude the sharing of alternative solutions that shape different experiences. Our virtual community of NPS prevention experts provides a flagship for ongoing collaboration between research, generation of evidence informing policy and practice, professional training, support and shared learning. It underscores the need for an innovative and multi-disciplinary approach to sharing perspectives in tackling emerging and harmful drug trends.